Nghiên cứu cố định Zr(IV) nồng độ cao trên hoạt tính theo phương pháp thủy nhiệt trong môi trường H2O2 để hấp phụ asen trong nước - Phương Thảo, Đào Thị; Trung, Đỗ Quang; Nội, Nguyễn Văn; Vân, Phạm Thị (Vietnam Journal of Chemistry, 2015)
New materials with high adsorption capacity based on Zr(IV) immobilition on activated carbon for the removal of As(III) in water have been investigated and synthesized following hydrothermal processe. The experimental results showed that Zr(IV) has been immobilized on activated carbon at 120 oC, pH = 2 for 14 hours in H2O2 medium can higher adsorb arsenic than free Zr(IV) immobilized one. The adsorption characteristics of material have been examined by the eqilibrium adsorption, time hydrothermal, temperature hydrothermal and effect of concentration of H2O2. The maxium adsorption capacity of material was 19,4 mg/g.  The obtained materials were characterized by X-ray diffraction (XRD), adsorption–desorption N2-isotherms (BET), thermogravimetric analysis (TGA) and energy dispersive X-ray spectroscopy (EDS).